Mae West : Empress of Sex - Leonard, Maurice (London Fontana, 1992)
Approaching fifty, a short, plump Brooklynite shot to international fame as an outrageous sex goddess. Her name was Mae West, and this is the story of her life and times. It recounts her upbringing in vaudeville, her connections with gangland, and her brief, but successful, film career.
Include Illustration and Index
Keywords: Motion picture actors and actresses -- United States -- West, Mae